Psychological Capital and Job Satisfaction Following the Return to In-Person Teaching for Professors in Economic Sciences at a Colombian University (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
The objective of this document is to analyze the psychological capital and job satisfaction of professors in the Faculty of Economic Sciences at a Colombian university following their return to in-person teaching. The research approach was quantitative, and data were obtained through a survey. Job satisfaction was investigated using the subscale developed by Warr et al. (1979), and psychological capital was measured using the Psychological Capital Questionnaire (PCQ) proposed by Luthans and Youssef (2007). From the sample, the structural equation model was employed, revealing positive and statistically significant correlations between the latent variables. Additionally, self-efficacy represents the highest value in Psychological Capital, while optimism is the lowest. Regarding Job Satisfaction, intrinsic job satisfaction has the highest estimator. Furthermore, the model yielded a B1 parameter estimator of 0.861 for the direct relationship between Psychological Capital and Job Satisfaction, validating the research hypothesis. This study allows the relationship between the variables to be corroborated through structural equations in other faculties of economic sciences in the country. Moreover, it is crucial that, based on this analysis, the human resources department of the university under study promotes clear strategies and programs to address variables such as optimism during times of crisis and internal job satisfaction.
Keywords: Psychological capital; Covid-19; teachers; job satisfaction